Hyperpolarized [1, 13C]pyruvate in lysed human erythrocytes: effects of co‐substrate supply on reaction time courses. (11th August 2014) - Pagès, Guilhem; Tan, Yee Ling; Kuchel, Philip W.
<x xml:space="preserve">Abstract</x> Hyperpolarized [1, 13C]pyruvate was injected rapidly into haemolysates in which hydrolysis of nicotinamide adenine dinucleotide (phosphate) (NAD(P))/NAD(P)H had been inhibited with nicotinamide. Haemolysates provide a stable glycolytic system in which membrane permeability is not a flux‐controlling step, and they enable the concentration of NADH to be adjusted experimentally while keeping the rest of the sample with the same composition as that of the cytoplasm of the cell (albeit diluted twofold at the time of injection of the [1, 13C]pyruvate). We showed that the maximum amplitude of the 13C NMR signal from the [1, 13C]l‐lactate, produced from [1, 13C]pyruvate, and the time at which it occurred was dependent on NADH concentration, as predicted by enzyme‐kinetic analysis. The main feature of such curves was dictated by the immediacy of the supply of the co‐substrate of lactate dehydrogenase (LDH, EC 1.1.1.27), and we posit that this also pertains in vivo in various tissues including neoplasms. By constructing an appropriate mathematical model and by using a Markov‐chain Monte Carlo approach, we fitted experimental data to estimate LDH and NADH concentrations. Experiments carried out with only endogenous NADH present enabled the estimation of its effective concentration in human RBCs; the ability to make this estimate is a special feature of the rapid‐dissolution dynamic nuclear polarization method. We found an endogenous NADH concentration in human RBCs two to four times higher than previously reported. Copyright © 2014 John Wiley & Sons, Ltd.